A transiting M-dwarf showing beaming effect in the field of Ruprecht 147. Issue 3 (8th August 2018) - Eigmüller, Philipp; Csizmadia, Szilárd; Endl, Michael; Gandolfi, Davide; Cochran, William D; Yong, David; Smith, Alexis M S; Cabrera, Juan; Deeg, Hans J; Johnson, Marshall C; Korth, Judith; Nespral, David; et al.
ABSTRACT: We report the discovery and characterization of an eclipsing M5Vdwarf star, orbiting a slightly evolved F7V main sequence star. In contrast to previous claims in the literature, we confirm that the system does not belong to the galactic open cluster Ruprecht 147. We determine its fundamental parameters combining K2 time-series data with spectroscopic observations from the McDonald Observatory, FIES@NOT, and HIRES@KECK. The very precise photometric data from the K2 mission allows us to measure variations caused by the beaming effect (relativistic doppler boosting), ellipsoidal variation, reflection, and the secondary eclipse. We determined the radial velocity using spectroscopic observations and compare it to the radial velocity determined from the beaming effect observed in the photometric data. The M5V star has a radius of 0.200 ^+0.007 _ -0.008 R⊙ and a mass of 0.187 ^+0.012 _ -0.013 M⊙ . The primary star has a radius of 1.518 ^+0.038 _ -0.049 R⊙ and a mass of 1.008 ^+0.081 _ -0.097 M⊙ . The orbital period is 5.441995 ± 0.000007 d. The system is one of the few eclipsing systems with observed beaming effect and spectroscopic radial velocity measurements and it can be used as a test case for the modelling of the beaming effect. Current and forthcoming space missions such as TESS and PLATO might benefit from the analysis of the beaming effect to estimate the mass of transiting companions without the need for radial velocity follow up observations, provided that the systematic sources of noise affecting this method are well understood.